Heterologous Expression of Panax ginseng PgTIP1 Confers Enhanced Salt Tolerance of Soybean Cotyledon Hairy Roots, Composite, and Whole Plants - An, Jing; Hu, Zhenmin; Che, Benning; Chen, Haiying; Yu, Bingjun; Cai, Weiming (Frontiers in Plant Science, 2017)
The Panax ginseng TIP gene PgTIP1 was previously demonstrated to have high water channel activity by its heterologous expression in Xenopus laevis oocytes and in yeast; it also plays a significant role in growth of PgTIP1-transgenic Arabidopsis plants under favorable conditions and has enhanced tolerance toward salt and drought treatment. In this work, we first investigated the physiological effects of heterologous PgTIP1 expression in soybean cotyledon hairy roots or composite plants mediated by Agrobacterium rhizogenes toward enhanced salt tolerance. The PgTIP1-transgenic soybean plants mediated by the pollen tube pathway, represented by the lines N and J11, were analyzed at the physiological and molecular levels for enhanced salt tolerance. The results showed that in terms of root-specific heterologous expression, the PgTIP1-transformed soybean cotyledon hairy roots or composite plants displayed superior salt tolerance compared to the empty vector-transformed ones according to the mitigatory effects of hairy root growth reduction, drop in leaf RWC, and rise in REL under salt stress. Additionally, declines in K+ content, increases in Na+ content and Na+/K+ ratios in the hairy roots, stems, or leaves were effectively alleviated by PgTIP1-transformation, particularly the stems and leaves of composite soybean plants. At the whole plant level, PgTIP1-trasgenic soybean lines were found to possess stronger root vigor, reduced root and leaf cell membrane damage, increased SOD, POD, CAT, and APX activities, steadily increased leaf Tr, RWC, and Pn values, and smaller declines in chlorophyll and carotenoid content when exposed to salt stress compared to WT. Moreover, the distribution patterns of Na+, K+, and Cl- in the roots, stems, and leaves of salt-stressed transgenic plants were readjusted, in that the absorbed Na+ and Cl- were mainly restricted to the roots to reduce their transport to the shoots, and the transport of root-absorbed K+ to the shoots was simultaneously promoted. PgTIP1 transformation into soybean plants enhanced the expression of some stress-related genes (GmPOD, GmAPX1, GmSOS1, and GmCLC1) in the roots and leaves under salt treatment. This indicates that the causes of enhanced salt tolerance of heterologous PgTIP1-transformed soybean are associated with the positive regulation on water relations, ion homeostasis, and ROS scavenging under